Analisis Pendapatan Lapak UMKM - Sherlin Indah Kusumaningtyas; Dhani Ichsanuddin Nur (IPM2KPE, 2022)
This study aims to analyze the effect of working capital on the profits of UMKM Stalls in Madiun City, to analyze financial processing to moderate the influence of working capital on the profits of UMKM Stalls in Madiun City. The research method uses a quantitative approach. The population in this study are all MSME stall owners in Madiun City. The sample of this research is 65 respondents which are calculated using the slovin formula. Data collection is done by distributing questionnaires. The data obtained is then tested through validity and reliability tests. The analysis technique was carried out using the SmartPLS (Partial Least Square) analysis method. The results showed that the working capital variable on the profits of UMKM stalls in Madiun City has a path coefficients value of 0.443653, and a T-statistic value of 2.942802 <1.96 (from the value table Zα = 0.05) or a P value of 0.004 < 0.05; b) the financial processing variable moderates the effect of working capital on profits 0.043 < 0.05, with the right results (positive or strengthening the relationship). In conclusion, working capital contributes to increasing UMKM profits in the UMKM Stalls in Madiun City, Financial Processing moderates working capital to contribute to the profits of UMKM in the UMKM Stalls in Madiun City. Keywords: UMKM Profits, Working Capital, Financial Processing, UMKM